Vacancy defects on optoelectronic properties of double perovskite Cs2AgBiBr6. (1st March 2021) - Chen, Hong; Zhang, Cai-Rong; Liu, Zi-Jiang; Gong, Ji-Jun; Wang, Wei; Wu, You-Zhi; Chen, Hong-Shan
Abstract: The commonly existed vacancy defects in semiconductors can affect optoelectronic properties. Here, to understand the vacancy defect influences on double perovskite Cs2 AgBiBr6, based upon density functional theory calculations and supercell model, we systematically investigated Cs, Ag, Bi, Br, Cs–Br and Ag–Br atomic pair vacancy effects on crystal structure, electronic structures, optical absorption, charge carrier and exciton binding energies. It was found that, the vacancy defects in double perovskite Cs2 AgBiBr6 induce slight deformation of crystal lattice. The vacancy defects cannot introduce extra defect states in the gap of energy band. The Cs, Ag, Bi, Ag–Br and Cs–Br defects not only change the band gap into the direct from the indirect of pristine system and reduce the band gap, but also promote the optical absorption capability, and result in red-shift of absorption spectra in low energy region. The Br vacancy leads to a heavy dopant character due to significant elevation of the Fermi level. The Cs, Ag, Bi, Ag–Br and Cs–Br vacancy defects also generate imbalanced charge transport properties, and increase exciton binding energies. Highlights: Vacancy defects cause small deformations of the crystal lattice. No defect state is found in the band gap after introducing vacancy defects. Vacancy defects promote light absorption and generate a red-shift. Vacancy defects can cause unbalanced charge transport properties.